Decentred regulation: The case of private healthcare in India. (July 2022) - Hunter, Benjamin M.; Murray, Susan F.; Marathe, Shweta; Chakravarthi, Indira
Highlights: The study of regulation in social sectors needs to recognise a wider range of state and non-state actors. Governments and statutory councils are important, but so too are accreditation companies, insurers, platform operators and consumer courts. Informal approaches based on individual and networked discretion also influence management and practice. Regulatory activities are performed in pursuit of actors' own interests, with implications for social equity. Adopting decentred approaches to studying regulation can shed light on these complex systems and their implications for social welfare. Abstract: In order to progress towards more equitable social welfare systems we need an improved understanding of regulation in social sectors such as health and education. However, research to date has tended to focus on roles for governments and professions, overlooking the broader range of regulatory systems that emerge in contexts of market-based provisioning and partial state regulation. In this article we examine the regulation of private healthcare in India using an analytical approach informed by 'decentred' and 'regulatory capitalism' perspectives. We apply these ideas to qualitative data on private healthcare and its regulation in Maharashtra (review of press media, semi-structured interviews with 43 respondents, and three witness seminars), in order to describe the range of state and non-state actors involved in setting rules and norms in this context, whose interests are represented by these activities, and what problems arise. We show an eclectic set of regulatory systems in operation. Government and statutory councils do perform limited and sporadic regulatory roles, typically organised around legislation, licensing and inspections, and often prompted by the judicial arm of the state. But a range of industry-level actors, private organisations and public insurers are involved too, promoting their own interests in the sector via the offices of regulatory capitalism: accreditation companies, insurers, platform operators and consumer courts. Rules and norms are extensive but diffuse. These are produced not just through laws, licensing and professional codes of conduct, but also through industry influence over standards, practices and market organisation, and through individualised attempts to negotiate exceptions and redressal. Our findings demonstrate regulation in a marketised social sector to be partial, disjointed and decentred to multiple loci, actively representing differing interests. Greater understanding of the different actors and processes at play in such contexts can inform future progress towards universal systems for social welfare.